Polyester film for dry film resist

By designing a polyester film with high intrinsic viscosity in a polyester film, combining the surface layer of 0.030-0.200μm particles and the particle-containing surface layer of 0.005-0.150μm particles, the dry film resist support film is solved in the circuit image formation. The transparency, flatness and sliding problems achieve efficient circuit image formation and resolution improvement.

CN111989618BActive Publication Date: 2024-12-13MITSUBISHI CHEM CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN201980026596.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-04-18
Filing Date
2019-04-15
Publication Date
2024-12-13
Estimated Expiration
2039-06-12

AI Technical Summary

Technical Problem

In the circuit image formation, the existing dry film resist support film is difficult to meet the high transparency, flatness, slippage and width direction thickness uniformity simultaneously, resulting in the problems of lower resolution and circuit defects.

Method used

A polyester film with an intrinsic viscosity of 0.65 dl/g or more was used, and a surface layer containing 0.030 to 0.200 μm particles on a single side was used, and a polyester layer containing 0.030 to 0.200 μm particles and 0.005 to 0.150 μm particles were used in a mass ratio of 10 to 7000 ppm. The particle-containing surface layer improves stretching magnification and flatness, and reduces thickness unevenness and air accumulation.

Benefits of technology

High flatness and transparency are achieved, the slipperiness and winding of the film are improved, circuit defects and resolution are reduced, and air accumulation and wrinkles are prevented.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GDA0004827261220000131
    Figure GDA0004827261220000131
  • Figure GDA0004827261220000331
    Figure GDA0004827261220000331
  • Figure GDA0004827261220000332
    Figure GDA0004827261220000332
Patent Text Reader

Abstract

Provided is a polyester film for dry film resist which can achieve high flatness and transparency, good film slip properties, little uneven thickness in the width direction of the film, can be wound up in a roll shape, and can prevent air from being trapped between films. The novel polyester film for DFR is characterized in that the polyester film comprises a base polyester film having an intrinsic viscosity of 0.65 dl / g or more and has a particle-containing surface layer on at least one side thereof, the base polyester film containing particles having an average particle size of 0.030 to 0.200 μm at a mass ratio of 10 to 7000 ppm, the film is a single layer composed of a polyester layer (referred to as "A layer") substantially free of particles having a particle size of 0.300 μm or more, or a multi-layer film having the A layer on the surface thereof, and the particle-containing surface layer contains particles having an average particle size of 0.005 to 0.150 μm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a polyester film used for forming a dry film resist (hereinafter sometimes abbreviated as "DFR"), and particularly to a polyester film which can be suitably used as a support film constituting the dry film resist. Background Art

[0002] Dry film resist (DFR) is widely used as a resist layer for forming wiring patterns of electronic circuit boards.

[0003] Dry film resist (DFR) generally has a three-layer structure consisting of a support film (also called a "carrier film"), a photoresist layer formed of a photosensitive resin material, and a protective film (also called a "cover film").

[0004] As a method for manufacturing an electronic circuit substrate using such a DFR, for example, a protective film is first peeled off from the DFR to expose the photoresist layer, and the aforementioned photoresist layer is overlapped on the copper layer surface of an epoxy resin substrate on which a copper layer is laminated, for example, and the DFR is affixed. Then, a supporting film is overlapped on a glass plate on which a circuit is printed to make the DFR close to it, and light is irradiated from the glass plate side.

[0005] The light is transmitted through the transparent portion of the circuit image printed on the glass plate and the inside of the supporting film layer, and then irradiated to the photoresist layer. The position of the photoresist layer irradiated with the light is cured by the light.

[0006] Next, after removing the glass plate and the supporting film, the uncured portion of the photoresist layer is removed and etching is performed using an acid or the like.

[0007] At this time, the uncured portion of the photoresist layer is removed to expose the copper layer at the corresponding position, and the exposed copper layer is removed from the epoxy resin substrate by etching, thereby forming a circuit on the epoxy resin substrate.

[0008] Then, by removing the cured photoresist layer, an electronic circuit substrate can be manufactured.

[0009] As the support film used for forming the DFR, a polyester film is mainly used because of its excellent mechanical properties, optical properties, chemical resistance, heat resistance, dimensional stability, flatness, and the like.

[0010] Regarding this polyester film, for example, Patent Document 1 discloses a biaxially oriented laminated polyester film, which contains particles with an average particle size of 0.01 to 3.0 μm in the outermost layer on at least one side, the center line average roughness Ra of the outermost layer is greater than 0.005 μm and the maximum height Rt is less than 1.5 μm, and the haze value is set to less than 1.5%.

[0011] Patent Document 2 discloses a laminated polyester film for a dry film resist that has excellent winding properties, can more reliably prevent the occurrence of circuit defects, and further improves resolution. The laminated polyester film comprises at least two polyester layers, and the number of metal-containing aggregates having a major diameter of 10 μm or more is 5 / 10 cm. 2 Hereinafter, at least one of the outermost layers contains particles having an average particle diameter of 0.01 to 3.0 μm, a center line average roughness Ra of the surface is 0.002 to 0.030 μm, and a maximum height Rt is 0.05 to 1.0 μm.

[0012] Patent Document 3 discloses a biaxially oriented polyester film for a dry film resist support, wherein the number of pit defects with a depth of 0.5 μm or more is 5 / m 2 The F-5 value in the longitudinal direction is 70 to 150 MPa, the F-5 value in the width direction is 80 to 160 MPa, the haze value is less than 1%, and the heat shrinkage rate at 150°C for 30 minutes is 1.5 to 3.5% in the longitudinal direction and 0.5 to 2.5% in the width direction.

[0013] Prior art literature

[0014] Patent Literature

[0015] Patent Document 1: Japanese Patent Application Laid-Open No. 7-333853

[0016] Patent Document 2: Japanese Patent Application Publication No. 2005-77646

[0017] Patent Document 3: Japanese Patent Application Publication No. 2008-239743 Summary of the invention

[0018] Problem that the invention aims to solve

[0019] In recent years, circuits formed by miniaturization of electronic devices have become extremely complex, lines have become thinner, and the spacing between them has become narrower, and DFR has been required to have higher reproducibility and resolution of image formation.

[0020] In DFR, exposure is performed by irradiating light to the photoresist layer through a supporting film. Therefore, if the transparency of the supporting film is low, the photoresist layer will not be fully exposed. In addition, if the haze value of the film is high or the surface is rough, the scattering of light on the surface and inside of the film may sometimes cause problems such as deterioration of resolution.

[0021] Therefore, the support film constituting the DFR is required to have a flatter surface and higher transparency.

[0022] However, when the flatness of the film increases, the film's sliding property deteriorates, the handling property deteriorates, and in addition, it may become difficult to wind the film into a roll.

[0023] Furthermore, when the flatness is improved and the thickness is uneven in the width direction of the film, air is easily trapped, which also causes wrinkles.

[0024] In order to improve the handling properties and winding characteristics of such a film, it is conceivable to include particles in the polyester film to form fine protrusions on the surface.

[0025] However, if protrusions are formed by adding particles, ultraviolet rays are scattered by the protrusions and depressions are generated on the surface of the resist layer, which can easily lead to a decrease in resolution and defects in the formation of ultra-fine line circuits or reduce the transparency of the film.

[0026] Thus, a method for obtaining a DFR film that satisfies transparency, flatness, slip properties, and thickness uniformity in the width direction at the same time has not yet been found.

[0027] Therefore, the present invention relates to a polyester film used for forming a DFR, and in particular, a polyester film that can be suitably used as a support film, and aims to provide a novel polyester film for a dry film resist, which can not only achieve high flatness and transparency, but also have good film slip properties, have little thickness unevenness in the width direction of the film, and can be wound into a roll, but also can prevent air from being trapped between the films.

[0028] Solutions for solving problems

[0029] The present invention provides a polyester film for dry film resist, characterized in that the polyester film is a polyester film for dry film resist having a particle-containing surface layer on at least one side of a base polyester film having an intrinsic viscosity of 0.65 dl / g or more.

[0030] The aforementioned base polyester film contains particles with an average particle size of 0.030 to 0.200 μm at a mass ratio of 10 to 7000 ppm, and is a single layer formed by a polyester layer (also called "A layer") that essentially does not contain particles with a particle size of 0.300 μm or more, or a multilayer film having the A layer on the surface, and the aforementioned particle-containing surface layer contains particles with an average particle size of 0.005 to 0.150 μm.

[0031] Effects of the Invention

[0032] The polyester film for dry film resist proposed by the present invention has a high intrinsic viscosity of the base polyester film, so the stretching ratio, especially the stretching ratio in the width direction, can be increased, and the thickness unevenness in the width direction of the film can be reduced.

[0033] As a result, the thickness of the film can be made uniform, and air accumulation can be prevented when the film is wound into a roll, thereby reducing the occurrence of wrinkles.

[0034] Furthermore, the polyester film for dry film resist proposed by the present invention comprises a polyester layer (A layer) containing particles having an average particle size of 0.030 to 0.200 μm at a mass ratio of 10 to 7000 ppm, and comprises a particle-containing surface layer containing particles having an average particle size of 0.005 to 0.150 μm, thereby achieving not only high flatness and transparency but also improved slip properties of the film, so that it can be wound into a roll.

[0035] In addition, scratches on the film can be reduced, and when used as a support film constituting a dry film resist, the problem of hindering the curing of the resist can be solved. DETAILED DESCRIPTION

[0036] Next, the present invention will be described based on an embodiment example. However, the present invention is not limited to the embodiment described below.

[0037] [Polyester film]

[0038] The polyester film for dry film resist (referred to as "the present polyester film") as an example of the embodiment of the present invention is a polyester film including a particle-containing surface layer on at least one side of a base polyester film.

[0039] <Polyester film as base material>

[0040] The base polyester film constituting the present polyester film (referred to as "the present base polyester film") preferably contains polyester as a main component resin and contains particles with an average particle size of 0.030 to 0.200 μm at a mass ratio of 10 to 7000 ppm, and is a single layer formed by a polyester layer (A layer) that does not substantially contain particles with a particle size of 0.300 μm or more, or a multilayer having the A layer on the surface, specifically, 2 layers, 3 layers, 4 layers or more layers.

[0041] When the base polyester film is a multi-layer film having a layer A on the surface, the main component resin of each layer other than the layer A is preferably polyester, and particularly preferably the same polyester as the main component resin of the layer A. Polyester will be described later.

[0042] Here, the "main component resin" means the resin having the highest content among the resins constituting each layer, and specifically means that the content of the resin in each layer is 50 mass % or more, more preferably 80 mass % or more, and particularly preferably 90 mass % or more.

[0043] When the base polyester film is a multilayer film having an A layer on the surface, specifically, A layer / B layer, A layer / B layer / A layer, etc., which have a polyester layer (also referred to as "B layer") as a main layer, can be cited. A layer / B layer / C layer, A layer / B layer / C layer / A layer, etc., which further have a different polyester layer (also referred to as "C layer") can also be cited. However, it is not limited to these.

[0044] (A floor)

[0045] The A layer contains the polyester described below as a main component resin and contains particles having a particle size of 0.030 to 0.200 μm at a mass ratio of 10 to 7000 ppm, and is a polyester layer that does not substantially contain particles having a particle size of 0.300 μm or more.

[0046] If the A layer constituting the single-layer substrate polyester film or the A layer as one or both surface layers of the substrate polyester film does not contain the particles, the handling property will be poor and multiple scratches may be introduced on the film surface during the polyester film forming process.

[0047] As described above, exposure is performed by irradiating the resist layer with light through the support film. Therefore, if there are foreign matter or scratches on the support film of the DFR, the portion is not exposed, resulting in circuit defects.

[0048] Therefore, when considering using the present polyester film as a support film of DFR, it is particularly preferred that the A layer forming the surface of the present base polyester film contains particles.

[0049] The average particle size of the particles contained in the A layer is preferably within a range of 0.030 μm to 0.200 μm.

[0050] If the average particle size of the particles is less than 0.200 μm, the transparency of the film will not be hindered. On the other hand, if the average particle size of the particles is greater than 0.030 μm, the surface of the film can be appropriately roughened, which not only improves the handleability but also prevents the introduction of scratches on the film surface during the film-making process of the base polyester film.

[0051] From this viewpoint, the average particle size of the particles contained in the A layer is preferably 0.030 μm to 0.200 μm, particularly preferably in the range of 0.040 μm or more and 0.150 μm or less, and particularly preferably in the range of 0.050 μm or more and 0.100 μm or less.

[0052] Therefore, the average particle size of the particles contained in layer A is preferably 0.030μm to 0.150μm or 0.030μm to 0.100μm, more preferably 0.040μm to 0.200μm, 0.040μm to 0.150μm or 0.040μm to 0.100μm, particularly preferably 0.050μm to 0.200μm, 0.050μm to 0.150μm or 0.050μm to 0.100μm.

[0053] It should be noted that the average particle size of the particles in each layer can be obtained by measuring the diameters of more than 10 particles using a scanning electron microscope (SEM) and calculating the average value thereof. In the case of non-spherical particles, the average value of the longest diameter and the shortest diameter can be measured as the diameter of each particle.

[0054] Furthermore, the A layer preferably does not substantially contain particles having a particle size of 0.300 μm or more from the viewpoint of maintaining light transmittance during exposure, eliminating circuit defects after exposure, and the like.

[0055] In this case, “does not contain substantially” means that the particles are not intentionally contained, and specifically, means that the content (mass) of the particles is 200 ppm or less, more preferably 150 ppm or less.

[0056] Furthermore, the A layer preferably contains particles having an average particle size of 0.030 μm to 0.200 μm as described above at a mass ratio (also referred to as “concentration”) of 10 to 7000 ppm.

[0057] In layer A, if the content of particles with an average particle size of 0.030 μm to 0.200 μm (particle concentration) is less than 7000 ppm, the transparency of the film can be improved. On the other hand, if the content of particles with an average particle size of 0.030 μm to 0.200 μm (particle concentration) is more than 10 ppm, the surface of the film can be made moderately rough, which not only improves the handleability but also prevents the introduction of scratches on the film surface during the film-making process of the base polyester film.

[0058] From this viewpoint, the A layer preferably contains particles having an average particle size of 0.030 μm to 0.200 μm at a mass ratio of 10 to 7000 ppm, more preferably 100 ppm or more or 6000 ppm or less, particularly 500 ppm or more or 5000 ppm or less, particularly 1000 ppm or more or 4000 ppm or less.

[0059] Therefore, for layer A, it is preferred that particles with an average particle size of 0.030 μm to 0.200 μm are contained in a mass ratio of 10 to 6000 ppm, 10 to 5000 ppm or 10 to 4000 ppm, and it is more preferred that they are contained in a mass ratio of 100 to 7000 ppm, 100 to 6000 ppm, 100 to 5000 ppm or 100 to 4000 ppm, and it is further preferred that they are contained in a mass ratio of 500 to 7000 ppm, 500 to 6000 ppm, 500 to 5000 ppm or 500 to 4000 ppm, and it is particularly preferred that they are contained in a mass ratio of 1000 to 7000 ppm, 1000 to 6000 ppm, 1000 to 5000 ppm or 1000 to 4000 ppm.

[0060] The material of the particles contained in the A layer is not particularly limited as long as the particles have an average particle size of 0.030 to 0.200 μm. Examples thereof include inorganic particles such as calcium carbonate, calcium phosphate, silicon dioxide, kaolin, talc, titanium dioxide, aluminum oxide, barium sulfate, calcium fluoride, lithium fluoride, zeolite, and molybdenum sulfide, organic particles such as ion exchange resins, cross-linked polymers, and calcium oxalate, and precipitated particles generated during polyester polymerization.

[0061] The particles contained in the A layer may be one kind or two or more kinds. Particles of the same kind but different in particle diameter and particle shape may be used simultaneously.

[0062] The shape of the particles may be any of spherical, blocky, rod-like, flat, or other shapes.

[0063] From the viewpoint of transparency and the like, the thickness of the A layer is preferably 0.1 to 20.0 μm, more preferably 0.3 μm or more and 10.0 μm or less, and particularly preferably 0.5 μm or more and 5.0 μm or less.

[0064] In addition, from the viewpoint of flatness, the ratio of the thickness (μm) of the A layer to the average particle size (μm) of the particles contained in the A layer is preferably 0.5 to 400, preferably 5 or more or 100 or less, and more preferably 10 or more or 50 or less.

[0065] (B layer)

[0066] The present base polyester film preferably has a polyester layer (B layer) as a main layer in addition to the above-mentioned A layer. In this case, in order to reduce costs and improve transparency, the B layer preferably contains no particles substantially or contains particles at a concentration at least lower than that of the A layer.

[0067] At this time, when the base polyester film has other layers in addition to the A layer, the "main layer" means the layer with the largest thickness among them.

[0068] The above-mentioned “does not contain substantially” means that the particles are not intentionally contained, and specifically, means that the particle content (particle mass concentration) is 200 ppm or less, more preferably 150 ppm or less.

[0069] The polyester as the main component resin of the B layer is preferably the same as the polyester as the main component resin of the A layer.

[0070] When the B layer contains particles, as described above, in order to reduce costs and improve transparency, the average particle size of the particles contained in the B layer is preferably smaller than the average particle size of the particles contained in the A layer, and is further preferably 0.010 μm to 0.200 μm, among which it is particularly preferred to be greater than 0.012 μm or less than 0.100 μm, and especially greater than 0.015 μm or less than 0.080 μm.

[0071] In addition, from the viewpoint of maintaining light transmittance during exposure and preventing circuit defects after exposure, the B layer preferably does not substantially contain particles having a particle size of 0.300 μm or more, similarly to the A layer.

[0072] Furthermore, as described above, in order to reduce costs and improve transparency, the particle concentration in layer B is preferably at least lower than the particle concentration in layer A, and specifically, it is preferably a mass ratio of 0 to 4000 ppm, among which it is further preferably less than 2000 ppm, especially less than 1000 ppm, especially less than 500 ppm, and most preferably less than 100 ppm.

[0073] The type and shape of the particles contained in the B layer are the same as those in the A layer.

[0074] The thickness of the B layer is preferably 0.1 to 40.0% of the thickness of the B layer, more preferably 1.0% or more and 20.0% or less, and particularly preferably 3.0% or more and 10.0% or less, from the viewpoint of improving transparency and reducing costs.

[0075] (C-layer)

[0076] As described above, when the present base polyester film has a C layer in addition to the A layer and the B layer, the C layer preferably has polyester as a main component resin and contains particles at a concentration at least lower than that of the A layer. Alternatively, it may be a layer containing particles like the A layer and having a different thickness from the A layer.

[0077] It should be noted that the types and shapes of particles in the C layer are the same as those in the A layer.

[0078] The thickness of the C layer is preferably 1 to 300% of the thickness of the A layer, more preferably 10% or more or 200% or less, and particularly preferably 20% or more or 150% or less, from the viewpoint of improving transparency and reducing costs.

[0079] (Polyester)

[0080] The polyester forming the main component resin of each layer of the polyester film is not particularly limited, as long as it is a polyester obtained from aromatic dicarboxylic acid or its ester and diol as main starting materials. Among them, polyesters having 60% or more of the repeating structural units having ethylene terephthalate units or ethylene 2,6-naphthalate units are preferred.

[0081] The polyester may contain a third component other than the ethylene terephthalate unit and the ethylene 2,6-naphthalate unit as a copolymerization component or a mixing component. For example, a resin compatible with the polyester resin such as polycarbonate may be mixed.

[0082] Examples of the aromatic dicarboxylic acid component include terephthalic acid, dimethyl terephthalate, 2,6-naphthalene dicarboxylic acid, isophthalic acid, phthalic acid, adipic acid, sebacic acid, etc. Among them, terephthalic acid or dimethyl terephthalate is particularly preferred.

[0083] Examples of the diol component include one or more of ethylene glycol, diethylene glycol, propylene glycol, and butylene glycol, among which ethylene glycol is particularly preferred.

[0084] When the above-mentioned polyester is a copolyester, as its dicarboxylic acid component, for example, one or more of isophthalic acid, phthalic acid, terephthalic acid, 2,6-naphthalene dicarboxylic acid, sebacic acid, etc. can be mentioned, and as its diol component, for example, one or more of ethylene glycol, diethylene glycol, propylene glycol, butanediol, 1,4-cyclohexanedimethanol, neopentyl glycol, etc. can be mentioned.

[0085] (Base material polyester film)

[0086] The polyester film of the present substrate preferably has an intrinsic viscosity of 0.65 dl / g or more.

[0087] If the intrinsic viscosity of the polyester film of the present base material is 0.65 dl / g or more, then as described later, even if the stretching ratio, especially the stretching ratio in the width direction (transverse direction), is increased to 4.0 times or more, it can be stretched without breaking. Therefore, the uneven thickness of the film, especially in the width direction, can be reduced, and air accumulation can be suppressed when winding into a roll, thereby reducing the occurrence of wrinkles.

[0088] From such a viewpoint, the intrinsic viscosity of the present substrate polyester film is preferably 0.65 dl / g or more, more preferably 0.65 dl / g or more and 0.90 dl / g or less, and particularly preferably 0.66 dl / g or more and 0.80 dl / g or less.

[0089] The intrinsic viscosity of the polyester film can be adjusted by appropriately changing the polymerization conditions of the polyester as the main component resin. For example, if the polymerization time is prolonged or the molecular weight is increased by solid phase polymerization, the intrinsic viscosity can be increased.

[0090] It should be noted that, when the present base polyester film is laminated, the above-mentioned intrinsic viscosity refers to the intrinsic viscosity of all the film layers.

[0091] The polyester film as the substrate may be a non-stretched film (sheet) or a stretched film, preferably a stretched film, and more preferably a biaxially stretched film.

[0092] When the laminated polyester film is a biaxially stretched film, it may be a sequentially biaxially stretched film or a simultaneously biaxially stretched film.

[0093] From the viewpoint of handling and economic efficiency, the thickness of the polyester film as the substrate is preferably 6 μm to 63 μm, more preferably 9 μm or more and 38 μm or less, and particularly preferably 12 μm or more and 25 μm or less.

[0094] <Surface layer containing particles>

[0095] The polyester film may have a structure in which the particle-containing surface layer is laminated on only one side of a base polyester film, or may have a structure in which the particle-containing surface layer is laminated on both sides of the base polyester film.

[0096] Furthermore, another layer may be laminated between the base polyester film and the particle-containing surface layer, or on the surface of the particle-containing surface layer.

[0097] When the base polyester film is composed of two layers, layer A and layer B, and the particle-containing surface layer is formed on only one side of the base polyester film, it is preferably formed on the side opposite to layer A, that is, layer B.

[0098] The particle-containing surface layer preferably contains particles having an average particle size of 0.005 to 0.150 μm.

[0099] If the average particle size of the particles contained in the particle-containing surface layer is greater than 0.005 μm, the slip and windability of the film can be appropriately maintained. If the average particle size is less than 0.150 μm, the particles become difficult to fall off from the particle-containing surface layer. In addition, the particle-containing surface layer is not easily ground, so it is preferred.

[0100] From this viewpoint, the particle-containing surface layer preferably contains particles having an average particle size of 0.005 to 0.150 μm, and more preferably contains particles having an average particle size of 0.010 μm or more and 0.120 μm or less, and particularly preferably contains particles having an average particle size of 0.030 μm or more and 0.100 μm or less.

[0101] Therefore, the particle-containing surface layer preferably contains particles of 0.005-0.120 μm or 0.005-0.100 μm, more preferably 0.010-0.150 μm, 0.010-0.120 μm or 0.010-0.100 μm, and particularly preferably 0.030-0.150 μm, 0.030-0.120 μm or 0.030-0.100 μm.

[0102] It should be noted that, if the average particle size of the particles contained in the particle-containing surface layer is within the above range, the particle-containing surface layer may contain particles having a particle size of less than 0.005 μm, or may contain particles having a particle size of greater than 0.150 μm.

[0103] The ratio of the average particle size of the particles contained in the particle-containing surface layer to the average particle size of the particles contained in the A layer is preferably 0.02 to 10, among which it is more preferably above 0.1 or below 5, especially above 0.3 or below 3, and it is further preferred that the average particle size of the particles contained in the particle-containing surface layer is larger than the average particle size of the particles contained in the A layer.

[0104] By making the above ratio satisfy the predetermined range, the flatness of the A layer and the slipperiness of the particle-containing surface layer can be satisfied at the same time, and a more suitable DFR film can be obtained.

[0105] The average particle size of the particles in the particle-containing surface layer can be determined by measuring the diameters of 10 or more particles using a scanning electron microscope (SEM) and taking the average value thereof. In the case of non-spherical particles, the average value of the longest diameter and the shortest diameter can be measured as the diameter of each particle.

[0106] The particle concentration in the particle-containing surface layer is preferably 1 to 10% by mass.

[0107] If the particle concentration in the particle-containing surface layer is 1% by mass or more, it can impart lubricity and improved winding effects. On the other hand, if it is 10% by mass or less, the particles become difficult to aggregate, which can reduce the grinding of the particle-containing surface layer caused by particle shedding, and is less likely to hinder the light transmission of the DFR film and less likely to cause circuit defects.

[0108] From such a viewpoint, the particle concentration in the particle-containing surface layer is preferably 1 to 10% by mass, more preferably 2% by mass or more and 7% by mass or less, and particularly preferably 2% by mass or more and 5% by mass or less.

[0109] The ratio of the particle concentration (mass %) in the particle-containing surface layer to the particle concentration (mass %) in the A layer is preferably 1 to 10,000, and preferably 5 or more or 1,000 or less, particularly preferably 10 or more or 100 or less.

[0110] By making the above ratio satisfy the predetermined range, the flatness and scratch resistance of the A layer and the slipperiness of the particle-containing surface layer can be satisfied at the same time, and a more suitable DFR film can be obtained.

[0111] The type and shape of the particles in the particle-containing surface layer are the same as those described for the particles contained in layer A. Among them, inorganic particles, particularly silica particles, are preferred.

[0112] (Antistatic Agent)

[0113] The particle-containing surface layer preferably further contains an antistatic agent.

[0114] When the support film laminated on the photoresist layer is peeled off, foreign matter such as dirt and dust is attracted to the photoresist layer and attached due to static electricity generated by the peeling charge, sometimes causing irregularities in the circuit pattern. Therefore, it is preferred to give the support film antistatic properties when peeling it off.

[0115] The particle-containing surface layer contains an antistatic agent, so that the polyester film can be made into a support film for a high-resolution dry film resist having a highly flat surface in contact with the photoresist layer and having mold release properties and antistatic properties.

[0116] The antistatic agent used in the particle-containing surface layer may include, for example, ammonium-containing compounds, polyether compounds, sulfonic acid compounds, betaine compounds and other ion-conductive polymer compounds, polyacetylene, polyphenylene, polyaniline, polypyrrole, polyisothianaphthene, polythiophene and other π-electron conjugated polymer compounds. It should be noted that the polyether compound is an antistatic agent and is also equivalent to the synthetic wax as the aforementioned release agent.

[0117] Among these, ion conductive polymer compounds are preferred, and ammonium-containing compounds are particularly preferred. The particle-containing surface layer formed by a coating solution containing π-conjugated conductive polymers, such as polythiophene and polyaniline, is usually strongly colored. DF films are preferably highly transparent (low haze), so π-conjugated conductive polymers are sometimes not suitable.

[0118] Furthermore, since π-conjugated conductive polymer coatings are generally more expensive than ion conductive coatings, an ion conductive antistatic agent may be preferably used from the viewpoint of production cost.

[0119] As the ammonium group-containing compound, a polymer compound having an ammonium group is preferred. For example, a polymer containing a monomer having an ammonium group and an unsaturated double bond as a component can be used.

[0120] Specific examples of the polymer include polymers having a constituent element represented by the following formula (1) as a repeating unit. The polymer may be a homopolymer or a copolymer obtained by copolymerizing other plural components.

[0121]

[0122] In the above formula (1), R 1 , R 2 Each independently represents a hydrogen atom, an alkyl group, a phenyl group, etc. These alkyl groups and phenyl groups may be substituted by the groups shown below.

[0123] The substitutable group is, for example, a hydroxyl group, an amide group, an ester group, an alkoxy group, a phenoxy group, a naphthoxy group, a thioalkoxy group, a thiophenoxy group, a cycloalkyl group, a trialkylammoniumalkyl group, a cyano group, a halogen group, and the like. 1 and R 2 Chemical bonding can be performed, for example -(CH2) m -(m=an integer from 2 to 5), -CH(CH3)CH(CH3)-, -CH=CH-CH=CH-, -CH=CH-CH=N-, -CH=CH-N=C-, -CH2OCH2-, -(CH2)2O(CH2)2-, etc.

[0124] In the case of a polymer having the constituent element represented by the above formula (1) as a repeating unit, it is preferred to copolymerize with other repeating units from the viewpoint of improving compatibility with other materials, improving the transparency of the resulting coating film, and further improving the demolding property. Examples of other repeating units include alkyl acrylates such as methyl acrylate, ethyl acrylate, propyl acrylate, and butyl acrylate, alkyl methacrylates such as methyl methacrylate, ethyl methacrylate, propyl methacrylate, and butyl methacrylate, and acrylamides such as N-hydroxymethyl acrylamide.

[0125] In the above formula (1), X - It can be appropriately selected within the range not impairing the gist of the present invention, and examples thereof include halogen ions, sulfonate, phosphate, nitrate, alkylsulfonate, and carboxylate.

[0126] In addition, a polymer obtained by copolymerizing the constituent element represented by formula (1) and a (meth)acrylate containing polyethylene glycol is preferred because the structure becomes flexible and a particle-containing surface layer having excellent uniformity can be obtained during in-line coating.

[0127] The number average molecular weight of the antistatic agent contained in the particle-containing surface layer is preferably 1,000 to 500,000, more preferably 2,000 or more and 350,000 or less, and particularly preferably 5,000 or more and 200,000 or less.

[0128] If the number average molecular weight of the antistatic agent is 1,000 or more, the strength of the coating film can be maintained, the heat resistance stability can be maintained, and sufficient antistatic properties can be obtained. In addition, if the molecular weight is 500,000 or less, the viscosity of the coating liquid can be prevented from increasing, the handling property and coating property can be well maintained, and it is suitable as a DFR film.

[0129] (wax)

[0130] The particle-containing surface layer preferably contains wax in order to improve the slipperiness of the film.

[0131] In this case, the antistatic agent may be contained together with the antistatic agent, or the wax may be contained without the antistatic agent.

[0132] Examples of the wax that may be contained in the particle-containing surface layer include plant waxes, animal waxes, mineral waxes, natural waxes such as petroleum waxes, synthetic hydrocarbons, modified waxes, and synthetic waxes such as hydrogenated waxes.

[0133] Among them, polyolefin compounds are preferred. Specifically, for example, a compound such as a polyolefin compound having a polymer or copolymer containing unsaturated hydrocarbons such as ethylene, propylene, 1-butene, 4-methyl-1-pentene, etc. is dissolved or dispersed as a basic skeleton compound, and examples thereof include polyethylene, polypropylene, poly-1-butene, poly-4-methyl-1-pentene, ethylene-propylene copolymer, ethylene-1-butene copolymer, propylene-1-butene copolymer, etc. More specifically, a polyolefin having an acid value of 10 to 50 and having an active hydrogen group at the end, and further oxidized polyethylene or oxidized polypropylene are preferably used.

[0134] When a polymer wax is used, the number average molecular weight thereof is preferably 2000 to 20000, and more preferably 3000 to 15000. Within such a range, film forming properties and mold releasability can be maintained.

[0135] The softening point is preferably 70 to 170° C., and more preferably 90° C. or higher and 150° C. or lower. Within such a range, film forming properties and mold releasability can be maintained.

[0136] (Crosslinking agent)

[0137] In order to improve the coating film strength of the particle-containing surface layer and impart abrasion resistance to the film, the particle-containing surface layer preferably further contains a crosslinking agent.

[0138] Examples of the crosslinking agent include melamine compounds, oxazoline compounds, epoxy compounds, isocyanate compounds, carbodiimide compounds, etc. Among these crosslinking agents, melamine compounds are preferred because of good coating strength and excellent releasability of the particle-containing surface layer.

[0139] In addition, these cross-linking agents may be used in combination of two or more types.

[0140] The melamine compound is a compound having a melamine skeleton in the compound, and for example, an alkylated melamine derivative, a compound partially or completely etherified by reacting an alcohol with an alkylated melamine derivative, and a mixture thereof can be used. As the alcohol used for etherification, methanol, ethanol, isopropanol, n-butanol, isobutanol, etc. can be suitably used.

[0141] The melamine compound may be a monomer or a dimer or higher polymer, or a mixture thereof may be used.

[0142] Furthermore, a compound obtained by co-condensing urea or the like with a part of melamine may be used, and a catalyst may be used to increase the reactivity of the melamine compound.

[0143] As above-mentioned oxazoline compound, the polymkeric substance that particularly preferably contains oxazoline group, can be made by the monomer containing addition polymerization property oxazoline group alone or with the polymerization of other monomers.The monomer containing addition polymerization property oxazoline group can enumerate 2-vinyl-2-oxazoline, 2-vinyl-4-methyl-2-oxazoline, 2-vinyl-5-methyl-2-oxazoline, 2-isopropenyl-2-oxazoline, 2-isopropenyl-4-methyl-2-oxazoline, 2-isopropenyl-5-ethyl-2-oxazoline etc., can use their one or more mixture of two kinds.

[0144] There are no restrictions on other monomers as long as they are monomers copolymerizable with the monomer containing an addition-polymerizable oxazoline group. Examples thereof include (meth)acrylates such as alkyl (meth)acrylates (as the alkyl group, methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, 2-ethylhexyl, and cyclohexyl); unsaturated carboxylic acids such as acrylic acid, methacrylic acid, itaconic acid, maleic acid, fumaric acid, crotonic acid, styrenesulfonic acid and its salts (sodium salt, potassium salt, ammonium salt, tertiary amine salt, etc.); unsaturated nitriles such as acrylonitrile and methacrylonitrile; (meth)acrylamide, N-alkyl (meth) Unsaturated amides such as (alkyl) acrylamide, N,N-dialkyl (meth) acrylamide (as the alkyl group, methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, 2-ethylhexyl, cyclohexyl, etc.); vinyl esters such as vinyl acetate and vinyl propionate; vinyl ethers such as methyl vinyl ether and ethyl vinyl ether; α-olefins such as ethylene and propylene; halogen-containing α,β-unsaturated monomers such as vinyl chloride and vinylidene chloride; α,β-unsaturated aromatic monomers such as styrene and α-methylstyrene, etc., and one or more of them can be used.

[0145] Examples of the epoxy compounds include condensates of epichlorohydrin with hydroxyl groups or amino groups of ethylene glycol, polyethylene glycol, glycerol, polyglycerol, bisphenol A, etc.; polyepoxy compounds, diepoxy compounds, monoepoxy compounds, glycidylamine compounds, and the like.

[0146] Examples of the polyepoxide include sorbitol polyglycidyl ether, polyglycerol polyglycidyl ether, pentaerythritol polyglycidyl ether, diglycerol polyglycidyl ether, triglycidyl tris(2-hydroxyethyl)isocyanate, glycerol polyglycidyl ether, and trimethylolpropane polyglycidyl ether. Examples of the diepoxide include neopentyl glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether, resorcinol diglycidyl ether, and ethylene glycol diglycidyl ether. Examples of the epoxy compounds include water glyceryl ether, polyethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, and polytetramethylene glycol diglycidyl ether. Examples of the monoepoxy compounds include allyl glycidyl ether, 2-ethylhexyl glycidyl ether, and phenyl glycidyl ether. Examples of the glycidylamine compounds include N,N,N',N'-tetraglycidyl-m-xylenediamine and 1,3-bis(N,N-diglycidylamino)cyclohexane.

[0147] It should be noted that the crosslinking agent is preferably used in the drying process and the film-forming process in order to react and improve the performance of the particle-containing surface layer. It is presumed that unreacted products of these crosslinking agents, reacted compounds, or mixtures thereof exist in the completed particle-containing surface layer.

[0148] (Binder)

[0149] For the particle-containing surface layer, in order to improve the adhesion to the polyester film of the substrate, etc., as a binder, it can contain thermoplastic resins such as polyesters, polyurethanes, acrylic resins, polyethylene resins, polyolefins and / or thermosetting resins such as thermosetting acrylic resins, melamine resins, epoxy resins, etc.

[0150] (Content ratio)

[0151] The mass ratio of the particles contained in the particle-containing surface layer to the antistatic agent, wax, binder, and crosslinking agent which may be further contained in the particle-containing surface layer is preferably appropriately adjusted according to the selected compounds, and the following is a standard.

[0152] The content of the particles in the particle-containing surface layer (particle concentration) is preferably 1% by mass or more, and more preferably 2% by mass or more and 10% by mass or less.

[0153] By making the content of particles in the particle-containing surface layer (particle concentration) greater than 1 mass %, it becomes easier to obtain the lubricity and improved winding effects of the DFR film. By making it less than 10 mass %, the particles become less likely to aggregate, which can reduce the grinding of the particle-containing surface layer caused by particle shedding, and is less likely to hinder the light transmission of the DFR film, making it less likely to cause circuit defects.

[0154] The content of the antistatic agent in the particle-containing surface layer is preferably 5% by mass or more, and more preferably 10% by mass or more or 90% by mass or less.

[0155] When the antistatic agent is a polymer of a compound having an ionic functional group, the content is preferably 15 to 90% by mass, and more preferably 20% by mass or more and 90% by mass or less.

[0156] By setting the content of the antistatic agent to be within the above range, a sufficient surface resistivity can be achieved, and the DFR film becomes less susceptible to electrostatic adhesion.

[0157] The wax content in the particle-containing surface layer is preferably 1% by mass or more, more preferably 2% by mass or more or 10% by mass or less. By making the wax content within the above range, sufficient slippery effect can be easily achieved, and adhesion with the polyester film substrate is not easily hindered.

[0158] The content of the crosslinking agent in the particle-containing surface layer forming composition constituting the particle-containing surface layer is preferably 1% by mass or more, and more preferably 2% by mass or more and 50% by mass or less.

[0159] When the content of the crosslinking agent is 1% by mass or more, the DFR film can be easily lubricated and the winding can be improved. When the content is 50% by mass or less, the light transmission of the DFR film is less likely to be blocked, and circuit defects are less likely to occur.

[0160] The content of the binder in the particle-containing surface layer is preferably 1% by mass or more, more preferably 2% by mass or more and 60% by mass or less. When the content of the binder is within the above range, sufficient adhesion to the polyester film substrate can be obtained.

[0161] (Other ingredients)

[0162] The particle-containing surface layer may also contain a defoamer, a coating improver, a thickener, an organic lubricant, an antistatic agent, an ultraviolet absorber, an antioxidant, a foaming agent, a dye, a pigment, etc., as needed.

[0163] The analysis of the components of the particle-containing surface layer can be performed by, for example, TOF-SIMS, X-ray photoelectron spectroscopy (XPS), fluorescent X-ray analysis, or the like.

[0164] (Film thickness including particle surface layer)

[0165] The film thickness of the particle-containing surface layer is preferably in the range of 0.001 μm to 0.5 μm, more preferably in the range of 0.005 μm or more and 0.3 μm or less, and particularly preferably in the range of 0.01 μm or more and 0.2 μm or less.

[0166] When the film thickness of the particle-containing surface layer is 0.5 μm or less, the coating film appearance and the cured state of the coating film can be maintained, and when the film thickness is 0.001 μm or more, sufficient mold releasability can be obtained.

[0167] In addition, when the film thickness of the particle-containing surface layer is 0.001 to 0.5 μm, the surface roughness of the laminated polyester film is not affected.

[0168] That is, the surface roughness of the dry film resist film and the surface roughness of the laminated polyester film can be regarded as the same.

[0169] The ratio of the film thickness (μm) of the particle-containing surface layer to the average particle diameter (μm) of the particles contained in the particle-containing surface layer is preferably 0.005 to 100.

[0170] When the ratio is 0.005 or more, the particles can be prevented from falling off, while when it is 100 or less, the surface protrusions caused by the particles can be maintained, so that the sliding property can be further improved, and the winding property can be improved.

[0171] From such a viewpoint, the ratio is preferably 0.005 to 100, more preferably 0.01 or more and 10 or less, and more preferably 0.1 or more and 1 or less.

[0172] The ratio of the film thickness (μm) of the particle-containing surface layer to the layer thickness (μm) of the A layer is preferably 0.00005 to 5, preferably 0.001 or more or 1 or less, and more preferably 0.01 or more or 0.1 or less.

[0173] <Method for producing the polyester film>

[0174] (Method for producing the present base polyester film)

[0175] First, the method for producing the base polyester film will be described.

[0176] For example, a raw material such as a polyester resin is melted by an extruder, and all layers of a mold (such as a T-die, etc.) are co-melted and extruded from a nozzle onto a rotating cooling drum, and then quenched to produce an unstretched laminated film. The unstretched laminated film is then stretched in the longitudinal and transverse directions and heat-fixed as needed.

[0177] At this time, the stretching ratio in the transverse direction, in other words, the width direction, is preferably 4.0 times or more, and the stretching ratio in the longitudinal direction is more preferably 2.5 times or more as necessary.

[0178] The intrinsic viscosity of the polyester film of the present substrate is above 0.65 dl / g, so high-ratio stretching, especially transverse stretching, can be implemented without breakage, which can reduce thickness unevenness and make the thickness uniform, thereby preventing air accumulation when winding into a roll and inhibiting the formation of wrinkles.

[0179] An example of a method for producing the present base polyester film including three layers of layer A / layer B / layer A will be described. The same applies to other laminated structures.

[0180] First, the polyester forming the A layer and the polyester forming the B layer are supplied to respective extruders, heated to a temperature above the melting point of each polyester, and melted, respectively. Next, the polyesters are extruded from a T-die in the form of a sheet so that the polyesters are stacked in the order of A / B / A.

[0181] Next, the sheet is rapidly cooled on a rotating cooling drum to a temperature below the glass transition temperature to obtain an amorphous unstretched film. At this time, in order to improve the planarity of the unstretched film, the adhesion between the unstretched film and the rotating cooling drum can be improved by electrostatic application densification method, liquid coating densification method, etc.

[0182] Next, the unstretched film is stretched in its length direction (longitudinal stretching) using a roll stretching machine to obtain a uniaxially stretched film. At this time, the stretching temperature is above the glass transition temperature of the polyester, preferably 70 to 150° C., and more preferably 75 to 130° C. In addition, the longitudinal stretching ratio is 2.5 times or more, more preferably 2.8 times or more or 4.0 times or less, and especially 3.0 times or more or 3.5 times or less. At this time, the longitudinal stretching can be performed in only one stage, or it can be performed in two or more stages.

[0183] Next, a tenter stretching machine is used to stretch the uniaxially stretched film in its width direction (transverse stretching) to obtain a biaxially stretched film. At this time, the stretching temperature is preferably 75 to 150°C, more preferably 80 to 140°C. In addition, the transverse stretching ratio is 4.0 times or more, preferably 4.2 times or more or 6.0 times or less, especially 4.4 times or more or 5.5 times or less, and more preferably 4.5 times or more or 5.0 times or less. At this time, transverse stretching can be performed in only one stage, or it can be performed in two or more stages.

[0184] Next, the biaxially stretched film is heat-treated at a temperature of, for example, 150 to 250° C., thereby producing a laminated film.

[0185] When the biaxially stretched film is subjected to heat treatment, the biaxially stretched film may be relaxed by 30% or less.

[0186] Then, roll it up into a roll as needed.

[0187] (Formation of particle-containing surface layer)

[0188] The particle-containing surface layer can be formed by "online coating" in which the film surface is treated during the production process of the present base polyester film, or by "offline coating" in which the particle-containing surface layer is coated outside the system on the temporarily produced present base polyester film.

[0189] In-line coating is a method of coating in the production process of the present substrate polyester film, specifically, a method of coating at any stage from the start of melt extrusion of the polyester to the end of stretching, heat fixing and winding up.

[0190] The coating is usually applied to any of an unstretched sheet obtained by melting and quenching, a uniaxially stretched film after stretching, a biaxially stretched film before heat setting, and a film after heat setting and before winding up.

[0191] For example, in the sequential biaxial stretching, a method in which the film is applied to a uniaxially stretched film stretched in the longitudinal direction (longitudinal direction) and then stretched in the transverse direction is particularly excellent.

[0192] According to the above method, since film formation and particle-containing surface layer formation can be performed simultaneously, there is an advantage in production cost.

[0193] Furthermore, since stretching is performed after coating, the film thickness of the particle-containing surface layer can be changed by the stretching ratio, and the coating film can be made thinner more easily than in offline coating.

[0194] Furthermore, by providing a particle-containing surface layer on the present base polyester film before stretching, the particle-containing surface layer can be stretched together with the present base polyester film. Thus, the particle-containing surface layer can be firmly adhered to the present base polyester film.

[0195] Furthermore, in the production of a biaxially stretched polyester film, the film ends are gripped with clips or the like and stretched, thereby constraining the film in the longitudinal and transverse directions, and applying a high temperature in the heat setting step while maintaining flatness without introducing wrinkles or the like.

[0196] Therefore, the heat treatment applied after coating can be set to a high temperature that cannot be achieved by other methods, so the film-forming property of the particle-containing surface layer is improved, and the particle-containing surface layer and the base film can be more firmly adhered.

[0197] Furthermore, a firm particle-containing surface layer can be formed, and the performance and durability of the particle-containing surface layer can be improved. Therefore, as a method for forming a particle-containing surface layer on at least one side of a polyester film, a manufacturing method is preferably performed in which a coating liquid is applied to the polyester film and then stretched in at least one direction.

[0198] As a method for forming a particle-containing surface layer, for example, the particles and the antistatic agent, wax, binder, cross-linking agent, etc. that the particle-containing surface layer may also contain can be dispersed or dissolved in a solvent to prepare a solution for the particle-containing surface layer, and then applied to one side of the substrate polyester film to form the particle-containing surface layer.

[0199] The particle-containing surface layer solution is preferably formed by coating one surface of the polyester film as a base material in the form of an aqueous coating liquid (a water-soluble resin or a water-dispersible resin using water as a medium).

[0200] However, it may also be formed by applying an aqueous coating liquid containing a small amount of an organic solvent.

[0201] Examples of the organic solvent include alcohols such as ethanol, isopropanol, ethylene glycol, and glycerol, ethers such as ethyl cellosolve, tert-butyl cellosolve, propylene glycol monomethyl ether, and tetrahydrofuran, ketones such as acetone and methyl ethyl ketone, esters such as ethyl acetate, and amines such as dimethylethanolamine. These can be used alone or in combination. In the aqueous coating liquid, these organic solvents are appropriately selected and contained as needed, so as to contribute to the stability, coating properties, or film properties of the coating liquid.

[0202] As a coating method for coating the particle-containing surface layer solution on the substrate polyester film, for example, a reverse roll coater, a gravure coater, a rod coater, an air doctor coater, or a coating device other than these as shown in "Coating Methods" written by Yuji Harasaki, published by Maki Shoten in 1979, can be used.

[0203] In the present polyester film, regarding the drying and curing conditions when forming a particle-containing surface layer on the polyester film, for example, when the particle-containing surface layer is set by off-line coating, it is usually better to heat treat it at 80 to 200° C. for 3 to 40 seconds, preferably at 100 to 180° C. for 3 to 40 seconds.

[0204] On the other hand, when the particle-containing surface layer is formed by in-line coating, it is generally preferred to perform heat treatment at 70 to 270° C. for 3 to 200 seconds.

[0205] In addition, whether the coating is performed offline or online, heat treatment and active energy ray irradiation such as ultraviolet ray irradiation may be used in combination as required. The surface of the laminated polyester film constituting the polyester film may be previously subjected to a surface treatment such as a corona treatment or a plasma treatment.

[0206] <This polyester film>

[0207] Next, the characteristics that the polyester film may have will be described.

[0208] (Surface roughness)

[0209] The average surface roughness (Ra) of the surface of the polyester film is preferably in the range of 0.001 to 0.020 μm, more preferably 0.002 μm or more and 0.010 μm or less, particularly preferably 0.002 μm or more and 0.005 μm or less.

[0210] When the surface roughness (Ra) of the polyester film is within the above range, the transparency of the polyester film is not impaired, and light scattering at the concavoconvex portions of the film surface is less likely to increase, thereby suppressing a decrease in ultraviolet (UV) exposure and preventing a decrease in resolution.

[0211] It should be noted that when the particle-containing surface layer is formed only on one side, it is preferably formed on the side of the base polyester film opposite to the side where the photoresist layer is formed. Therefore, the surface of the base polyester film, i.e., layer A, preferably has the above-mentioned average surface roughness (Ra).

[0212] Next, the same applies to Rt described below.

[0213] The average surface roughness (Rt) of the polyester film is preferably in the range of 0.010 to 0.400 μm, more preferably 0.015 μm or more and 0.300 μm or less, particularly 0.020 μm or more and 0.200 μm or less, particularly 0.025 μm or more and 0.100 μm or less.

[0214] If the maximum surface roughness (Rt) of the surface of the polyester film is less than 0.400 μm, it is possible to prevent the concave-convex transfer to the photoresist layer, and the problem of circuit defects caused when forming a fine-pitch circuit can be eliminated. On the other hand, if the maximum surface roughness (Rt) is more than 0.001 μm or the maximum surface roughness (Rt) is more than 0.010 μm, it is suitable for the manufacturing process, especially the film-making process, so that the surface of the DFR film is not easy to be scratched. Furthermore, it is not easy to produce scratch transfer and exposure scattering to the photoresist layer caused by the scratch, and it is not easy to affect the fine-pitch circuit pattern, so it is preferred.

[0215] (Haze)

[0216] The haze of the polyester film is preferably 1.0% or less, more preferably 0.1% or more or 0.7% or less, and particularly preferably 0.2% or more or 0.5% or less, from the viewpoint that the exposure to ultraviolet rays is less likely to become insufficient, defects in the desired circuit are less likely to be caused, and a decrease in resolution can be suppressed when used for a high-resolution DFR.

[0217] (Antistatic Properties)

[0218] The surface resistivity of the polyester film is preferably 2.0×10 13 Ω / □ or less, and more preferably 1.0×10 7 Ω / □ or more or 1.0×10 12 Ω / □ or less.

[0219] By setting the surface resistivity of the polyester film to 2.0×10 13 Ω / □ or less, so that it is easy to control the peeling charge when the DFR is wound into a roll.

[0220] Therefore, it is not easy to be charged, and the spark discharge caused by peeling charging can be suppressed. In addition, in the process of forming the photoresist layer, the adhesion of dirt and dust caused by charging can be prevented, and the formation defects of the photoresist layer and foreign matter defects after UV exposure can be prevented. In particular, in DFRs that require high resolution, there is a concern that even small foreign matter can become a defect in the circuit, so this problem can be suppressed.

[0221] By forming the particle-containing surface layer, the lubricity can be improved, and by incorporating an antistatic agent into the particle-containing surface layer, the antistatic property can be further improved.

[0222] <How to use this polyester film>

[0223] The polyester film can be suitably used as a support film for a dry film resist. For example, a photoresist layer can be laminated on at least one side of the polyester film as a support film, and a protective film can be laminated as needed to form a photosensitive laminate (e.g., DFR).

[0224] Therefore, the photosensitive laminate (for example, DFR) as an example of the embodiment of the present invention has a configuration in which a photoresist layer is laminated on at least one surface of the polyester film.

[0225] At this time, when the particle-containing surface layer is formed only on one side of the present base polyester film, when forming the DFR, in order to make the particle-containing surface layer located on the side opposite to the photoresist layer forming side, in other words, in order to make the surface of the present base polyester film on the opposite side to the particle-containing surface layer, i.e., layer A, closely adhere to the photoresist layer, it is preferred that the present polyester film is laminated on the photoresist layer.

[0226] The photosensitive laminate (eg DFR) generally has a laminate structure of support film / photoresist layer / protective film. When the DFR is rolled up, the lower surface of the DFR, that is, the support film, contacts the upper surface side of the protective film.

[0227] Therefore, when there is a particle-containing surface layer on the face in contact with the protective film, the effect of the slipperiness becomes remarkable. In addition, by not having a particle-containing surface layer on the anti-corrosion surface, the adhesion between the anti-corrosion layer and the support film is not easy to change, and it is not easy to peel off poorly when removing the support film from the anti-corrosion layer.

[0228] The photoresist layer constituting the dry film resist is formed of a photosensitive resin material and is cured by reacting with light such as ultraviolet rays.

[0229] Specific examples of the photosensitive resin material include alkali-soluble polymers such as carboxylic acid-containing vinyl copolymers, ethylenically unsaturated addition-polymerizable monomers such as 2-hydroxy-3-phenoxypropyl acrylate, and photopolymerization initiators such as benzyl dimethyl ketal.

[0230] The protective film constituting the photosensitive laminate (eg, DFR) is made of polyolefin such as polyethylene and polypropylene, polyester, etc., and is laminated on the opposite surface of the laminate film in the photoresist layer to protect the dry film resist.

[0231] <Description of statement, etc.>

[0232] "Sheet" generally refers to a flat product that is thin and whose thickness is smaller than its length and width according to the definition in JIS, and "film" generally refers to a thin and flat product whose thickness is very smaller than its length and width and whose maximum thickness is arbitrarily limited, and generally refers to one supplied in the form of a roll (Japanese Industrial Standard JIS K6900). However, the boundary between sheet and film is not defined, and there is no need to distinguish between the two in language in the present invention. Therefore, in the present invention, "film" also includes "sheet", and "sheet" also includes "film".

[0233] In addition, when expressed as a "panel" such as an image display panel, a protective panel, etc., it includes a plate body, a sheet, and a film.

[0234] In the present specification, when "X to Y" (X and Y are arbitrary numbers) is described, unless otherwise specified, it includes the meaning of "X or more and Y or less" as well as "preferably greater than X" or "preferably less than Y".

[0235] In addition, when it is recorded as "X or more" (X is an arbitrary number), unless otherwise specified, it includes the meaning of "preferably greater than X", and when it is recorded as "Y or less" (Y is an arbitrary number), unless otherwise specified, it also includes the meaning of "preferably less than Y".

[0236] Example

[0237] Hereinafter, the present invention will be described in further detail by way of examples, but the present invention is not limited to the following examples unless the gist of the present invention is exceeded.

[0238] <Material for forming base polyester>

[0239] In Examples and Comparative Examples, the following polyesters were used to prepare base polyesters (A layer and B layer).

[0240] (Polyester resin I)

[0241] 100 parts by mass of dimethyl terephthalate and 60 parts by mass of ethylene glycol were used as starting materials. Tetrabutyl titanate was added in such a manner that the content in terms of titanium atoms became 10 ppm by mass concentration. The mixture was taken to a reactor. The reaction start temperature was set to 150°C. Methanol was distilled off and the reaction temperature was slowly raised to 230°C after 3 hours. After 4 hours, the transesterification reaction was substantially terminated. The reaction mixture was transferred to a polycondensation tank and subjected to a 4-hour polycondensation reaction. The polymer was discharged in the form of strands under nitrogen pressure, cooled and flaked to obtain polyester flakes. The polyester flakes were then solid-phase polymerized at 220°C under vacuum to obtain polyester resin I.

[0242] The intrinsic viscosity of the polyester resin I is 0.70 dl / g.

[0243] (Polyester resin II)

[0244] 100 parts by mass of dimethyl terephthalate, 60 parts by mass of ethylene glycol and 0.09 parts by mass of magnesium acetate tetrahydrate were placed in a reactor, heated and methanol was distilled off to carry out an ester exchange reaction. Here, the temperature was raised to 230° C. over 4 hours from the start of the reaction, and the ester exchange reaction was substantially completed.

[0245] Next, spherical alumina particles were added in the form of ethylene glycol slurry. After the slurry was added, 0.03 parts by mass of phosphoric acid was further added, and antimony trioxide was added in such a manner that the content calculated as antimony atoms became 330 ppm by mass concentration, and a polycondensation reaction was performed to obtain polyester resin II. The intrinsic viscosity of polyester resin II was 0.61 dl / g.

[0246] At this time, the spherical alumina particles did not contain particles having a particle size of 0.300 μm or more, and the content of the spherical alumina particles was 1.5% by mass based on the entire polyester resin II.

[0247] (Polyester resin III)

[0248] In the preparation of polyester resin II, polyester resin III was obtained in the same manner as polyester resin II except that amorphous fine silica particles were added instead of spherical alumina particles. The intrinsic viscosity of polyester resin III was 0.61 dl / g.

[0249] At this time, the amorphous fine silica particles did not contain particles having a particle size of 0.300 μm or more, and the content of the amorphous fine silica particles was 0.3% by mass based on the entire polyester resin III.

[0250] (Polyester resin IV)

[0251] In the preparation of polyester resin II, polyester resin IV was obtained in the same manner as polyester resin II except that ion exchange resin particles were added instead of spherical alumina particles. The intrinsic viscosity of polyester resin IV was 0.61 dl / g.

[0252] At this time, the ion exchange resin particles include particles having a particle size of 0.300 μm or more, and the content of the ion exchange resin particles is 0.5% by mass based on the entire polyester resin IV.

[0253] (Polyester resin V)

[0254] In the preparation of polyester resin II, polyester resin V was obtained in the same manner as polyester resin II except that spherical alumina particles were not added and antimony trioxide was changed so that the content in terms of antimony atoms became 240 ppm by mass. The intrinsic viscosity of polyester resin V was 0.63 dl / g.

[0255] <Particle-Containing Surface Layer Forming Composition>

[0256] The following raw materials were used. In the following Examples and Comparative Examples, these raw materials were blended at the mass ratios shown in the tables to prepare coating liquids as particle-containing surface layer-forming compositions.

[0257] Antistatic agent (A1)

[0258] Polydiallyldimethylammonium chloride (number average molecular weight: about 30,000)

[0259] Wax (B1)

[0260] Into an emulsifying device with a capacity of 1.5 L and equipped with a stirrer, a thermometer and a temperature controller, 300 g of oxidized polyethylene wax with a melting point (softening point) of 105°C, an acid value of 16 mgKOH / g, a density of 0.93 g / mL and a number average molecular weight of 5,000, 650 g of ion exchange water, 50 g of decaglycerol monooleate surfactant and 10 g of a 48% potassium hydroxide aqueous solution were added. After replacing with nitrogen, the device was sealed and stirred at high speed at 150°C for one hour. The device was then cooled to 130°C and passed through a high-pressure homogenizer at 400 atmospheres to obtain a wax emulsion cooled to 40°C.

[0261] Particles (C1): Silica particles with an average particle size of 0.05 μm

[0262] Particles (C2): Silica particles with an average particle size of 0.08 μm

[0263] The average particle diameter of particles (C1) to (C2) was determined using a transmission electron microscope (H7650 manufactured by Hitachi High-Tech Corporation, accelerating voltage 100 kV).

[0264] ·Aqueous dispersion (D1)

[0265] An acrylic resin aqueous dispersion having a glass transition temperature of 40°C polymerized according to the following composition

[0266] Emulsified polymer of ethyl acrylate / n-butyl acrylate / methyl methacrylate / N-methylol acrylamide / acrylic acid = 65 / 21 / 10 / 2 / 2 (mass %) (emulsifier: anionic surfactant)

[0267] Cross-linking agent (E1): Hexamethoxymethylolmelamine

[0268] <Example 1>

[0269] As the A layer containing particles, polyester resin I and polyester resin II were mixed at a mass ratio of 85:15, melted by an extruder, and supplied to the A layer of the lamination die. As the main layer, i.e., the B layer, polyester resin I was melted by an extruder and supplied to the B layer of the lamination die. Two kinds of three-layer laminated polyester resins formed by the structure of A layer / B layer / A layer were coextruded in a film form and cast on a cooling drum at 35° C. to prepare a rapidly cooled and solidified unstretched film.

[0270] Next, the unstretched film was preheated with a heating roller at 75°C, and then stretched 3.2 times in the longitudinal direction between rollers at 85°C using a combination of an infrared heater and a heating roller. Then, a coating liquid prepared as a particle-containing surface layer forming composition according to the formulation shown in the following Table 1 was applied online to one side of the longitudinally stretched film. Next, the film ends were gripped with clips and introduced into a tenter, heated at a temperature of 95°C and stretched 4.5 times in the transverse direction, and heat-treated at 225°C for 10 seconds to produce a polyester film (sample) having a thickness of 16.0 μm (A layer / B layer / A layer=1.0 μm / 14.0 μm / 1.0 μm) and a width of 1580 mm, and having a particle-containing surface layer with a thickness of 0.030 μm on the surface of the substrate polyester film.

[0271] <Examples 2, 3, Comparative Examples 1, 2, 3, 4>

[0272] Except having changed the raw material of the base polyester film as shown in Tables 1 and 2, a polyester film (sample) was prepared in the same manner as in Example 1.

[0273] <Comparative Example 5>

[0274] A polyester film (sample) was prepared in the same manner as in Example 1 except that the particle-containing surface layer was not formed.

[0275] <Measurement Method and Evaluation Method>

[0276] The materials, substrate polyesters, and polyester films (samples) used in the above-mentioned Examples and Comparative Examples were measured and evaluated as follows.

[0277] (1) Thickness of polyester film (μm)

[0278] The thickness of the polyester film (sample) was measured using a micrometer.

[0279] (2) Thickness of each layer (layer A and layer B) of the base polyester film and thickness of the particle-containing surface layer

[0280] The thickness of each layer (A layer and B layer) of the polyester film substrate and the thickness of the particle-containing surface layer were measured by observing a cross section of the film using a transmission electron microscope (TEM).

[0281] Specifically, first, a small piece of a thin film sample is embedded in a resin obtained by mixing an epoxy resin with a curing agent and an accelerator, and a slice with a thickness of 200 nm is prepared using an ultramicrotome to prepare a sample for observation.

[0282] The obtained sample was observed using a transmission electron microscope (H-9000) manufactured by Hitachi High-Tech Corporation. In the observed cross section, the interface between the A layer and the B layer and the interface between the surface of the base polyester film and the particle-containing surface layer were observed by light and dark in a direction substantially parallel to the base polyester film.

[0283] The distance from the interface to the film surface was measured for 50 transmission electron microscope photos, and 10 points with larger and smaller measured values ​​were deleted, and the average of 30 points was used as the measured value. The thickness of each layer and the particle-containing surface layer thickness were calculated based on the average value.

[0284] In the transmission electron microscope, the acceleration voltage was set to 300 kV, and the magnification was set within a range of 10,000 to 100,000 times according to the thickness of the surface layer.

[0285] (3) Average surface roughness of the film surface (Ra)

[0286] The average surface roughness (Ra) of the film surface on the side opposite to the particle-containing surface layer was determined as follows using a surface roughness measuring instrument (SE-3F) manufactured by Kosaka Laboratory Co., Ltd.

[0287] That is, from the film cross-sectional curve obtained by measurement, a portion of the reference length L (2.5 mm) is extracted in the direction of its center line. When the center line of the extracted portion is taken as the x-axis and the longitudinal magnification direction is taken as the y-axis and the roughness curve y = f(x) is expressed, the value given by the following formula is expressed as [μm].

[0288] The centerline average roughness was expressed by obtaining 10 cross-sectional curves from the sample film surface and the average centerline average roughness of the extracted portion obtained from these cross-sectional curves. It should be noted that the tip radius of the stylus was set to 2 μm, the load was set to 30 mg, and the cutoff value was set to 0.08 mm.

[0289] (4) Maximum height of film surface (Rt)

[0290] The maximum height (Rt) of the film surface on the side opposite to the particle-containing surface layer was measured as follows.

[0291] For the extracted part of the cross-sectional curve obtained during Ra measurement, when the extracted part is clamped by two straight lines parallel to its average line, the interval between the two straight lines is measured in the direction of the longitudinal magnification of the cross-sectional curve, and the value expressed in micrometer (μm) is taken as the maximum height (Rt) of the extracted part.

[0292] Regarding the maximum height, 10 cross-sectional curves are obtained from the surface of the sample film, and the average value of the maximum heights of the extracted parts obtained from these cross-sectional curves is used.

[0293] (5) Average particle size (μm)

[0294] The average particle size of the particles in each layer is determined as follows: 10 or more particles are observed with a scanning electron microscope (SEM), the diameters of the particles are measured, and the average value thereof is obtained. In the case of non-spherical particles, the average value of the longest diameter and the shortest diameter is measured as the diameter of each particle.

[0295] (6) Particle concentration of polyester film

[0296] In the polyester film (sample), a sample is cut from the layer where the particle concentration is to be measured, and a solvent in which the polyester is dissolved but the particles are not dissolved is selected for dissolution treatment. The particles are then centrifuged from the solution and the mass ratio (ppm) relative to the total mass of the particles is measured as the particle concentration.

[0297] (7) Intrinsic viscosity

[0298] About 0.25 g of the freeze-crushed substrate polyester film was dissolved in about 25 mL of a mixed solvent of phenol / 1,1,2,2-tetrachloroethane (mass ratio 1 / 1) at 120°C for 30 minutes to a concentration of 1.00 g / dL, and then cooled to 30°C. The falling seconds of the sample solution and the solvent alone were measured at 30°C using a fully automatic solution viscometer (manufactured by SENTECH, "DT553"), and the intrinsic viscosity was calculated using the following formula (1).

[0299] Intrinsic viscosity = ((1 + 4K H η sp ) 0.5 -1) / (2K H C) Formula (1)

[0300] Here, η sp =η / η0-1, η is the falling seconds of the sample solution, η0 is the falling seconds of the solvent only, C is the concentration of the sample solution (g / dL), K H is the Huggins constant. K H Use 0.33.

[0301] (8) Film haze

[0302] The haze of the polyester film (sample) was measured using an integrating sphere turbidimeter NDH-20D manufactured by Nippon Denshoku Industries, Ltd. in accordance with JIS K 7105:1981.

[0303] (9) Static friction coefficient and dynamic friction coefficient

[0304] According to ASTM-D1894 (1999), two polyester films (samples) were prepared, and the static friction coefficient and the dynamic friction coefficient of the upper surface and the lower surface of the polyester film (sample) were measured.

[0305] (10) Antistatic properties

[0306] The polyester film (sample) was fully humidified in a measurement atmosphere of 23°C and 50% RH, and then the surface resistivity of the particle-containing surface layer of the substrate film was measured using a high resistance measuring device: HP4339B and a measuring electrode: HP16008B manufactured by Hewlett-Packard Company of Japan, after applying a voltage of 100 V for 1 minute. Based on the surface resistivity, the antistatic property was evaluated according to the following criteria.

[0307] ○ (good): surface resistivity is 1×10 12 Ω / □ or less

[0308] △(General): Surface resistivity is greater than 1×10 12 Ω / □ and 2×10 13 Ω / □ or less

[0309] ×(bad): surface resistivity greater than 2×10 13 Ω / □

[0310] (11) Scratch resistance of substrate film surface

[0311] Separately, a base film not having a particle-containing surface layer was prepared, and the surface of the base film was visually inspected and evaluated according to the following criteria.

[0312] ○ (good): No scratches were observed in the inspection range.

[0313] × (poor): Multiple scratches were observed within the inspection range.

[0314] (12) Grinding properties of particle-containing surface layer

[0315] An aluminum plate with a width of 10 mm and a length of 50 mm was brought into contact with the particle-containing surface layer of the polyester film (sample), a weight of 50 g was placed on the aluminum plate, and the aluminum plate was moved back and forth 10 times between 100 mm in parallel with the width direction of the aluminum plate. The two ends of the particle-containing surface layer surface where the aluminum plate was moved were observed under a microscope and judged according to the following criteria.

[0316] ○ (good): Grinding of the particle-containing surface layer was hardly observed.

[0317] × (poor): The surface layer containing particles was ground and much white powder was observed.

[0318] (13) Coiling

[0319] The polyester film (sample) was prepared into a roll of 1000 mm wide x 6000 m long, and the roll was wound up at a speed of 100 m / min using a winder. The appearance of the wound roll was visually inspected and evaluated according to the following criteria.

[0320] ○ (good): The polyester film (sample) has no wrinkles, and the roll end surfaces are neatly aligned.

[0321] △ (normal): The roll end surfaces are aligned, but the polyester film (sample) has small wrinkles.

[0322] × (bad): The polyester film (sample) meanders in the middle of rolling up the roll, or the polyester film (sample) has large wrinkles.

[0323] (14) Productivity

[0324] When a polyester film (sample) stretched 4.5 times or more in the transverse direction was continuously produced, the number of breaks (film ruptures) that occurred was determined according to the following criteria.

[0325] ○ (good): less than once a day on average

[0326] △(Normal): More than once and less than 3 times a day on average

[0327] ×(Poor): More than 3 times a day on average

[0328] (15) Evaluation of thickness unevenness

[0329] A polyester film (sample) was cut out from a roll with a width of 1000 mm, and 5 films were overlapped. The thickness was measured at 20 equal positions with a width of 1000 mm using a micrometer. The thickness at each position was divided by the number of overlapped sheets, and the difference in thickness between adjacent positions was taken as the thickness unevenness, and judged according to the following criteria.

[0330] ○ (good): The difference in thickness is less than 0.50 μm

[0331] △ (normal): The difference in thickness is 0.50 μm or more and less than 1.00 μm

[0332] × (bad): The difference in thickness is 1.00 μm or more

[0333] [Table 1]

[0334]

[0335] [Table 2]

[0336]

[0337] According to the results of the above-mentioned embodiments and comparative examples, as well as the test results conducted by the inventors so far, it can be known that by setting the intrinsic viscosity of the base polyester film to above 0.65 dl / g, even if the stretching ratio, especially the stretching ratio in the width direction, is set to 4.5 times or more, it is possible to stretch without breakage, thereby reducing the uneven thickness of the film in the width direction, making the thickness of the film uniform, and preventing air accumulation when winding into a roll, thereby reducing the formation of wrinkles.

[0338] It can also be seen that by setting the average particle size of the particles contained in layer A forming the surface layer of the substrate polyester film to 0.030 to 0.200 μm and setting its mass concentration to 10 to 7000 ppm, and simultaneously forming a particle-containing surface layer containing particles with an average particle size of 0.005 to 0.150 μm, the flatness and transparency of the film can be further improved. Despite this, the slipperiness of the film can still be improved, so that it can not only be wound into a roll, but also scratches can be reduced.

Claims

1. A polyester film for dry film resist, characterized in that: The polyester film for dry film resist comprises a base polyester film having an intrinsic viscosity of 0.65 dl / g or more and a particle-containing surface layer on at least one side thereof. The base polyester film is a single layer formed of a polyester layer (layer A) substantially free of particles having a particle size of 0.300 μm or more, or a multilayer film having the layer A on the surface, wherein substantially free of particles means that the content of particles having a particle size of 0.300 μm or more is 200 ppm or less, and the layer A contains particles having an average particle size of 0.030 to 0.200 μm at a mass ratio of 2250 to 7000 ppm. The particle-containing surface layer contains particles with an average particle size of 0.030 to 0.100 μm.

2. The polyester film for dry film resist according to claim 1, wherein The particle-containing surface layer also includes either or both of an antistatic agent and a wax.

3. The polyester film for dry film resist according to claim 1 or 2, wherein When the base polyester film is a multi-layer film having the A layer on the surface, the base polyester film has the A layer only on one side and has the particle-containing surface layer on the side opposite to the A layer.

4. A method for producing a polyester film for dry film resist, characterized in that: The method for producing a polyester film for a dry film resist according to any one of claims 1 to 3, wherein the base polyester film is stretched in the width direction at a stretching ratio of 4.0 times or more. 5 . A photosensitive laminate comprising a photoresist layer laminated on at least one surface of the polyester film for dry film resist according to claim 1 .

Citation Information

Patent Citations

  • Laminated polyester film for photoresist

    JP1995333853A

  • Layered polyester film for dry film resist

    JP2005077646A

  • Polyester film for dry film resist carrier

    JP2008239743A

  • Polyester film for high resolution dry film resist

    CN1806000A